Profil Pemecahan Masalah Siswa SMP Ditinjau Dari Persepsi Matematika (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
The purpose of this study was to determine the problem solving of junior high school students seen from the perception of mathematics. This type of research is a qualitative descriptive study with data collection techniques by providing perception instruments, problem solving tasks (TPM) to students and interview guidelines. After knowing the perceptions of each student, namely positive perceptions and negative perceptions. Each student worked on the problem solving task (TPM) and then an interview was immediately conducted regarding the results of the student's work. In this study, two female students with different perceptions were selected. The assessment of student problem solving is based on four indicators of understanding the problem, planning problem solving, implementing the plan, and re-checking the results of problem solving. The results of this study indicate that problem solving students with positive and negative perceptions have the same level of ability, but they work on the TPM slightly differently according to the comprehension of each student with different durations of time